2012
DOI: 10.1177/0269215512455532
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of adult stroke survivors and their parent carers: a qualitative study

Abstract: Parents reported adjusting to caring with relative ease. Survivors did not adjust to being cared for with such ease and felt positioned in a child role. Balancing independence and dependence was a challenge for survivors and parents and is considered within a systemic theory framework. Implications for service developments and guidelines are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
2
35
0
4
Order By: Relevance
“…The emotional impact of stroke was noted by Gosman-Hedström and Dahlin-Ivanoff 3 who found that mastering an uncertain, unpredictable life was the dominant theme for older females caring for partners with stroke, whereas a study by Jones and Morris 30 of adult stroke survivors and their parent carers highlighted carers' emotional turmoil, including chronic grief and distress.…”
Section: Summary Of Main Fi Ndingsmentioning
confidence: 99%
“…The emotional impact of stroke was noted by Gosman-Hedström and Dahlin-Ivanoff 3 who found that mastering an uncertain, unpredictable life was the dominant theme for older females caring for partners with stroke, whereas a study by Jones and Morris 30 of adult stroke survivors and their parent carers highlighted carers' emotional turmoil, including chronic grief and distress.…”
Section: Summary Of Main Fi Ndingsmentioning
confidence: 99%
“…Families often then take on the primary role of caregiver 26,27 ; may be left to grapple with cognitive and behavioural changes, and required to reorganise their everyday life to adjust to their new role [27][28][29] . Considering the extent of responsibility families have in caring for their loved one following brain injury 26 , one might presume that families would be well informed regarding the brain injury and potential behavioural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Keluarga penderita strok merasa bahwa mereka berkewajiban secara moral, dan tidak punya pilihan selain untuk menerima peran caregiver dan mereka menganggap caregiver sebagai 'bagian integral dari kehidupan' dan sebagai 'tugas yang tidak dapat dihindari' (Jones & Morris, 2012).…”
Section: Pembahasanunclassified
“…Stres, marah, temperamen, melukai perasaan, putus asa, ketidaknyamanan, dan kejenuhan adalah beberapa konsekuensi emosional negatif dari caregiver (Jullamate, dkk., 2006;Pierce, 2001;Pierce, dkk., 2012;Jones & Morris, 2012).…”
Section: Penelitian Yang Dilakukan Oleh Arksey Danunclassified
See 1 more Smart Citation